Dampak Intervensi Kesehatan terhadap Luaran Obstetrik dan Perinatal pada Kehamilan Remaja: Tinjauan Literatur Sistematis - Tantri Wenny Sitanggang; Suryo Ediyono (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Adolescent pregnancy is associated with increased risks of obstetric complications (anemia, preeclampsia, and delivery problems) and adverse perinatal outcomes such as low birth weight, prematurity, and neonatal death. Specific health interventions, including nutritional supplementation, counseling, health education, and group based antenatal care (ANC), have been proposed to mitigate these risks. This study aimed to identify and analyze the impact of specific health interventions including nutritional supplementation, counseling, group ANC, and health education on obstetric and perinatal outcomes in adolescent pregnancies through a systematic literature review (SLR). This review followed the PRISMA 2020 framework, encompassing four stages: identification, screening, eligibility, and inclusion. Articles were searched from Scopus and Google Scholar using defined keywords. Of 241 records identified, 41 full-text articles were reviewed, and 7 met the inclusion criteria (quantitative studies or systematic reviews evaluating specific interventions among pregnant adolescents). Nutritional supplementation, particularly iron and folic acid, effectively reduced anemia and improved birth weight. Counseling and health education enhanced adolescents’ knowledge, attitudes, and ANC compliance. Group ANC models reduced low birth weight and preterm birth while promoting social support. Specific health interventions significantly improve obstetric and perinatal outcomes among adolescent pregnancies. Further experimental studies with rigorous designs are needed to strengthen causal evidence.